Rethinking Electoral Democracy through Islamic Epistemology: Electoral Perception, Epistemic Justice, and Democratic Legitimacy - Masduri, Masduri; Hadinata, Fristian; Adian, Donny Gahral (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2026)
Electoral democracy is commonly evaluated through procedural criteria, whereas the epistemic conditions that shape citizens’ political judgments remain insufficiently theorized. This article addresses this gap by reconceptualizing electoral perception as an epistemic structure through which political knowledge is formed prior to electoral choice. Employing a normative-conceptual approach, it synthesizes social epistemology, Miranda Fricker’s theory of epistemic injustice, and Islamic epistemology to examine how political knowledge is produced, transmitted, verified, recognized, and critically evaluated within electoral contexts. The analysis demonstrates that electoral perception is constituted through testimony, trust, epistemic authority, credibility, and epistemic justice, while informational distortion and unequal distributions of credibility undermine democratic legitimacy by weakening citizens’ epistemic agency. The article develops an Islamic Ethics of Electoral Perception grounded in six interrelated principles—ṣidq, amānah, shahādah, tabayyun, ‘adl, and epistemic muḥāsabah—as a normative framework for evaluating political knowledge. It argues that democratic legitimacy depends not only on procedural fairness but also on an epistemically just environment that enables citizens to exercise responsible political judgment as epistemic agents.